Idiopathic Hemolacria: a case report - Jha, A (Journal of Psychiatrists’ Association of Nepal, 2020)
Hemolacria or bloody tears is a rare condition resulting from local and systemic causes. Most of the time cause remains unknown and is inferred to be psychogenic in nature. Management includes identification of the cause along with psycho-social intervention. Here I report a rare presentation of bloody tears in a 16 year adolescent female admitted in our inpatient facility with history and discussion.